Pengaruh Kompetensi Guru Terhadap Kinerja Guru di SMP Al-Washliyah 8 Medan - Rinaldi Hutasuhut (Jurnal Multidisiplin Madani, 2022)
The purpose of this study was to determine the effect of gut competence on teacher performance at SMP Al-Washliyah 8 Medan. The sample in this study amounted to 40 respondents, the data collection technique used was a questionnaire. Data processing using SPSS Version 24.0 for windows. The data analysis technique used is Simple Linear Regression, and to find out how much influence teacher competence has on teacher performance at SMP Al-Washliyah 8 Medan. The results of the simple linear regression test obtained the equation, Y = 3.876 + 0.476X, where teacher competence has a significant influence on teacher performance at SMP Al-Washliyah 8 Medan, the coefficient of determination is obtained at 0.607 which means that the teacher competency variable affects teacher performance in SMP Al-Washliyah 8 Medan by 60.7%. To find out whether the hypothesis is accepted in this study, the technique used partially on the independent variable is the teacher competency variable (X) which has a t count of 7.666 > 1.68595, meaning that it has a positive and significant effect on teacher performance. So Ha is accepted because t count > t table. Therefore, it can be concluded that teacher competence or independent variables have a significant influence on teacher performance at SMP Al-Washliyah 8 Medan.